New-onset bullous pemphigoid following the fifth dose of the COVID-19 vaccine Pfizer-BioNTech: A case report - Eman Badawod (SAGE Open Medical Case Reports, 2025)
Bullous pemphigoid is recognized as the most prevalent autoimmune blistering skin disease. This report presents a case of a 54-year-old male in Canada who developed new-onset bullous pemphigoid 4 weeks after receiving his fifth COVID-19 vaccine booster (Pfizer-BioNTech). The patient initially presented with a generalized erythematous rash, which progressed despite treatment with topical and systemic corticosteroids. He later developed tense blisters and peripheral eosinophilia, with a skin biopsy confirming the diagnosis of bullous pemphigoid. Although bullous pemphigoid has previously been linked to various vaccinations, the underlying mechanisms remain uncertain. Notably, cases of bullous pemphigoid flare-ups have been reported in patients with existing bullous pemphigoid after receiving mRNA COVID-19 vaccines. This report underscores the importance of considering new-onset bullous pemphigoid in patients presenting with blistering skin conditions following COVID-19 vaccination.